Aprendizagem organizacional como ferramenta de competitividade da empresa Irmãos Seibert & Cia Ltda. - Puhl, Paulo (2006)
The objective of this dissertation was to investigate as displayed the inherent factors organizational learning in the model of fifth disciplines of Peter M. Senge had been adopted in the company Irmãos Seibert & Cia. Ltda. This company was chosen by being one of small great of the industrial segment that possess an interesting evolution differential to the long one of the time. The importance of this study justifies why the complexity of the current context in constant change in result of the process of globalization economic and social, has demanded of organizations, different abilities of those privileged ones in the mechanist age of organizations. The search of development alternatives, interview adaption of practice innovative indispensable for survival changes imposed for a highly competitive market, it passes for the learning that if became one of the ability-key for survival and development of organizations. Amongst the managemental models that if present, aiming at to improve the capacities of learning of organizations, the model is distinguished of fifth disciplines, for its emphases in the human element in organizations, using as estimated, that organizations are in essence, product of thinking and interacting of its members. Of this form, it was adopted as method of investigation the case study, that learnig made possible to explore relative aspects qualitative in organizes, where the data had been collected interview half-structuralized carried through with dicrection of the structuralized company and questionaries applied to employes of the organization. To get the result in this work, the data had been compared and analyzed of the model of the five disciplines and other concepts constant correlations to the subject of the base theoretician-empiricist. In this direction the research disclosed that the theoreticians rules of organizations of learning in all the levels of organization, although informally. The lack of a professional of the knowledge for legalizes for the organizacional learning, verified in the research, if it understands as limiter factor of creates and spreads dissemination of the organizational knowledge.